Zemacrosaldula, a new genus of Saldidae (Hemiptera: Heteroptera) from New Zealand: taxonomy, geographic distribution, and biology - Larivière, Marie-Claude; Larochelle, André (Zootaxa, 2015)
Zemacrosaldula, new genus, is described with Salda australis White, 1876, as type species, resulting in the following new combination Zemacrosaldula australis (White, 1876). Three new species are described: Zemacrosaldula kapekape new species, Z. whakarunga new species, Z. pangare new species. A revision of the taxonomy of all taxa is presented. Species are keyed. Morphological descriptions are provided together with illustrations emphasising the most significant diagnostic features of external morphology and male genitalia. Information is given on synonymy, type specimens, material examined, geographic distribution and biology.